SOCIALIZATION OF DIGITAL MARKETING OF AGRICULTURAL PRODUCTS IN RIANGGEDE VILLAGE, TABANAN, BALI - Pratiwi, Nuning Indah; Arimbi, Diah Putri; Satria, Wahyu Indra (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Rianggede Village is located in Penebel District, Tabanan Regency, Bali Province. One of the goals in carrying out trading activities is to make a profit. Therefore, it takes a marketing effort that business actors must carry out to achieve goals. The application of the Internet network as a medium for promotion and transactions in marketing is one of the contributions to the development of information technology. Digital marketing is a term used to describe the process of using digital technology. Digital marketing promotes products and services using online digital media such as social networks. This service aims to introduce digital marketing through social media and marketplaces to the public, especially farmers. The 2023 University of National Education community service activity is a work program activity by conducting socialization activities related to digital marketing to farmers with the aim that the marketing of agricultural products from Rianggede Village will develop and be able to compete in the digital era.